Knowledge Management Practices in the Preparation and Performance of General Budgets: A Case Study of the Federal General Budget of the Republic of Iraq (2015-2017) - Hassan Mustafa Ali; Mustafa Othman Al-Sayegh (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The organizations of today's world recognize that knowledge has become necessary to realize it, which requires the management of knowledge or the so-called mental or mental power to contain and absorb all the surrounding changes. All other aspects of power today do not need special efforts to obtain them. The importance of knowledge management is not limited to private business, but rather to public activities of government or non-profit organizations. Hence, it is necessary to acquire, generate, develop knowledge and develop the cognitive role of the relation to success in general. The study, entitled "Role of Knowledge Management in the Preparation and Performance of Public Budgets", examines the state of the federal budget of the Republic of Iraq (2015-2017), considering that the budget is the most important tool in the development of people's lives. The presentation of the Iraqi federal budget through its laws, the use of performance description tools, analysis of results and presentation of a range of conclusions and recommendations related to the study.Keywords: The exchange trade, Growth domestic product, export, import, Russia-Turkey.